2011
DOI: 10.1074/jbc.m111.264754
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 Activates Synthesis of Interleukin-6 by Interfering with a KH-type Splicing Regulatory Protein (KSRP)-dependent Translational Silencing Mechanism

Abstract: Inflammatory gene expression is controlled by post-transcriptional mechanisms. Many relevant transcripts contain AU-rich elements (AREs) 4 that can impose rapid degradation and restrict translation (1-3). Several proteins that interact with and mediate the effects of AREs have been identified. One of them, heterogeneous nuclear ribonucleoprotein K homology (KH)-type splicing regulatory protein (KSRP) is a member of the far upstream sequence element-binding proteins (4). It is a single-stranded nucleic acid-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
39
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 43 publications
3
39
1
Order By: Relevance
“…A number of studies including our own have demonstrated that IL-1, a central mediator of inflammation, can induce stabilization of certain mRNAs, which encode proteins involved in inflammatory and immune reactions. More recently, we observed that IL-1 also activates translation of distinct mRNAs (2,3). We now present evidence that translation of several of its target mRNAs is also activated by the proinflammatory cytokine IL-17.…”
mentioning
confidence: 58%
See 1 more Smart Citation
“…A number of studies including our own have demonstrated that IL-1, a central mediator of inflammation, can induce stabilization of certain mRNAs, which encode proteins involved in inflammatory and immune reactions. More recently, we observed that IL-1 also activates translation of distinct mRNAs (2,3). We now present evidence that translation of several of its target mRNAs is also activated by the proinflammatory cytokine IL-17.…”
mentioning
confidence: 58%
“…Although several pathways, including NF-B and MAP kinase pathways, appear to contribute to transcriptional activation, it is well established that part of the effects of IL-17 on gene expression is caused by stabilization of mRNAs (12,13). Stabilization of cyclooxygenase-2 mRNA was found to depend on p38 MAP kinase (14), whereas CXCL1 (KC) mRNA was stabilized independently of p38 MAP kinase and of AU-rich elements (AREs) 3 (15,16), through a mechanism that, according to most recent evidence, involves inducible IB kinase, TRAF5, and SF2 (17,18). In this study, we provide evidence that IL-17 can induce proteins by activating translation of distinct target mRNAs, including those of IB and MCPIP1.…”
mentioning
confidence: 99%
“…6). This datum may help further our understanding of the molecular functions of FBP2, which is molecularly significant for translation (35,61), RNA stability (41,42), and miRNA biogenesis (43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, AUF1 and TIAR control translation of MYC mRNA (32). Recently, the ELAV protein HuD and KSRP were implicated in ARE-mRNA translational regulation (14,19).…”
mentioning
confidence: 99%